2014
DOI: 10.1002/2013jg002449
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale estimation and uncertainty analysis of gross primary production in Tibetan alpine grasslands

Abstract: Gross primary production (GPP) is an important parameter for carbon cycle and climate change research. Previous estimations of GPP on the Tibetan Plateau were usually reported without quantitative uncertainty analyses. This study sought to quantify the uncertainty and its partitioning in GPP estimation across Tibetan alpine grasslands during 2003-2008 with the modified Vegetation Photosynthesis Model (VPM). Monte Carlo analysis was used to provide a quantitative assessment of the uncertainty in model simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 68 publications
(106 reference statements)
1
25
0
Order By: Relevance
“…It has been reported that 94% of globally retrieved EVI values fall within the theoretical MODIS one‐sigma error bar [± (0.02 + 0.02 × value)], indicating that the error in a given index value is 0.02 plus 2% of the index value (Vermote & Kotchenova, ). Similar to other studies (Lin et al ., ; He et al ., ), we thus used 0.02 + 0.02 × value as standard error for EVI data.…”
Section: Methodsmentioning
confidence: 97%
“…It has been reported that 94% of globally retrieved EVI values fall within the theoretical MODIS one‐sigma error bar [± (0.02 + 0.02 × value)], indicating that the error in a given index value is 0.02 plus 2% of the index value (Vermote & Kotchenova, ). Similar to other studies (Lin et al ., ; He et al ., ), we thus used 0.02 + 0.02 × value as standard error for EVI data.…”
Section: Methodsmentioning
confidence: 97%
“…The amount of variability of the three NDVI dataset used in the calculation was more important than the specific mathematical operations, which was also illustrated in Lauenroth et al (2006). If the model is very sensitive to an input with very small uncertainty, then the uncertainty contribution of this input might be small, and vice versa (He et al, 2014). For example, the larger uncertainty in regions with lower biomass could be attributed to the greater variability among three NDVI datasets.…”
Section: Uncertainty Partitioning In Grassland Biomass Estimationsmentioning
confidence: 99%
“…Mean annual temperature (MAT, ºC) and mean annual precipitation (MAP, mm) for each study site were derived from the meteorological database produced by CERN (He et al, 2014). At each plot, soil samples were taken at depths of 0-10 cm using a 6 cm diameter auger and were sieved to remove roots and visible organic debris.…”
Section: Environmental Datamentioning
confidence: 99%